DETERMINANTS OF SHARIA BANKING MARKET SHARE GROWTH IN INDONESIA - Nizar Hosfaikoni Hadi; Muh. Khairul Fatihin (Airlangga International Journal of Islamic Economics and Finance, 2018)
AbstractThe purpose of this paper is to investigate the variables that influence Islamic banking markets in Indonesia. The research data were obtained directly from the website of the Central Statistics Agency (BPS) and the financial services authority(OJK) from 2011-2018 which were taken on a quarterly basis. This study uses multiple regression analysis to analyze the factors that have an impact on the market share of Islamic banks in Indonesia. The variable that can affect Islamic banking marketshare in Indonesia is the liquidity ratio (FDR). While other variables such as the default rate (NPF), profit rate (ROA), economic growth (GDP) and conventional bank interest rates (INT) do not affect Islamic banking. The results suggest that Islamic banking regulates liquidity ratios (FDR) so that Islamic banking can effectively increase its market. This study complements previous research so that Islamic banking maintains a liquidity ratio in order to remain balanced.Keywords: marketshare, Islamic banking, FDR, GDP, ROA